Effective, simple, easy procedure for laparoscopic port closure in difficult cases - Lasheen, Ahmed E. (Ann Med Surg (Lond), 2016)
BACKGROUND: Laparoscopic and rebotic surgery is widely practiced in modern medicine. The operative procedure is not complete until the port sites are closed with a fascial closure. Good fascial closure still represents problem, especially in difficult obese patients. This study reported simple technique is suitable in such cases. MATERIAL AND METHODS: We herein describe a simple technique for fascial closure after Laparoscopic surgery using percutaneous transabdominal approach by using two looped needles in 87 obese patients. This technique was done while the trocar sheath in its position. RESULTS: The procedure was used in 87 patients (69 females and 18 males) after laparoscopic cholecystectomy with mean body mass index 35.5 kg/m2 and mean age 47.1 years from May 2013 through June 2015. No intra-operative incidents and no port sites hernias were reported during a mean follow up of 18 months. CONCLUSION: The procedure is easy to perform, safe, and effective for fascial port site closure in difficult obese (thick abdominal wall and oblique port wound) cases.